Who is safe to extubate in the neuroscience intensive care unit? - Bösel, Julian (Seminars in respiratory and critical care medicine, 2017)
Patients admitted to the neuroscience intensive care unit (NICU) may have respiratory compromise from either central or peripheral neurological pathology, and may hence require intubation and mechanical ventilation for very diverse reasons. Liberation from invasive ventilation, that is, extubation, at the earliest possible time is a widely accepted principle in intensive care. For this, classic extubation criteria have been established in the general critical care setting, mainly targeting pulmonary function and cooperativeness of the patient. However, classic extubation criteria have failed to predict successful extubation in many studies on NICU patients, and extubation failure (EF) rates range between ∼20 and 40% in these. Not necessarily impaired consciousness, but neurological impairment of securing the airway and handling secretions (dysphagia, low pharyngeal muscle tone, weak cough, etc.) may be mainly responsible for this dilemma. Attempts have been made to identify predictors of EF or success, and to establish extubation scores for the NICU, but results have been partially controversial and the database is still weak. It is very important to have a stepwise protocol to approach extubation in the NICU patient and to be prepared for reintubation (at times in a difficult airway) and alternatives (such as tracheostomy). The particular challenges of safely extubating the NICU patient will be the focus of this review, including a suggestion for a standardized approach.
Gesehen am 17.09.2018